Does Knee Prosthesis Survivorship Improve When Implant Designs Change? Findings from the Australian Orthopaedic Association National Joint Replacement Registry. Issue 6 (June 2020) - Lewis, Peter L.; Graves, Stephen E.; de Steiger, Richard N.; Campbell, David G.; Peng, Yi; Hatton, Alesha; Lorimer, Michelle
Abstract: Background: TKA generally has excellent long-term survivorship. When a new knee system supersedes a previous model, increased survivorship, improved functional performance, or both may be expected, because key areas of design modification are often targeted to address wear, stability, and the patellofemoral articulation. However, not all design changes are beneficial, and to our knowledge, knee arthroplasty has not been systematically evaluated in the context of design changes that occur during the development of new knee arthroplasty systems. Questions/purposes: Using the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) we performed multiple old-to-new comparisons of frequently used contemporary knee implants to ask: (1) does overall prosthesis survivorship free from revision increase when a new knee prosthesis system is introduced to replace a prior prosthesis system? (2) Has survivorship free from revision improved for the revision indications of wear, instability, and patellofemoral articulation issues, where development efforts have been concentrated? Methods: Data from the AOANJRR from September 1999 to December 2017 were used to compare the survivorship of prostheses free from revision at a maximum of 17 years in procedures where a new design model was introduced to replace a prior knee system from the same manufacturer. Only prosthesis systems used in a minimum of 2000 primary TKA procedures for osteoarthritis that had a minimum of 5 years of follow-up were included. Varus-valgus constrained and hinge TKA designs were excluded. Cruciate-retaining, posterior-stabilized, and medial pivot-design knees were considered separately. The new and old prosthesis systems were paired for analysis. Survivorship was calculated with Kaplan Meier estimates and comparisons were performed using the Cox proportional hazards method. Subanalyses according to the three main revision indications were performed, and where possible, analyses were performed based on polyethylene types (highly cross-linked polyethylene and ultra-high-molecular-weight polyethylene), combined and separated. Revision was defined as a reoperation of a previous knee arthroplasty in which one or more of the components was removed, replaced, or added. There were 323, 955 TKA procedures and 11 new prosthesis system designs that were introduced to replace an earlier knee system from the same manufacturer. Of these prosthesis system pairs, six were cruciate-retaining prostheses, four were posterior-stabilized designs, and one was a medial pivot design. Results: Six of the 11 knee system pairs showed improved survivorship with the new design, three were no different, and in two, the newer prosthesis systems had a higher rate of revision than the old one did. When revision for wear was analyzed, five prosthesis systems showed improvement, five were no different, and one had a higher rate of revision than the previous system did. There was no improvement in the rate of revision for instability; seven new prosthesis systems showed no difference from the previous system and four new prosthesis systems had a higher rate of revision than the previous system did. A subanalysis of revision for patellofemoral complications showed improvement in two comparisons, no difference in six, and a higher revision rate in two; one could not be calculated because of an insufficient number of revisions for this reason. Conclusions: It is difficult to predict whether a new system will demonstrate better survival than a previous one, and widespread uptake of a new design before a benefit is shown in robust clinical studies is unwise. Similarly, adoption of a new system for which there is no difference in survivorship from a previous model may be premature because a new device may have associated unknown and unintended consequences. Healthcare policy makers and therapeutic device regulators should similarly be guided by results and seek out peer-reviewed evidence before accepting change to established practice. Surgeons must be aware that implant changes may not translate into better survivorship and must seek compelling evidence of improvement in survival and/or function before changing systems. Level of Evidence: Level III, therapeutic study.